BDCA2 plays a central role in the binding, internalization and response of plasmacytoid dendritic cells to vidutolimod - Lemke-Miltner, Caitlin D.; Blackwell, Sue E.; Yin, Chaobo; Fischer, Travis D.; Weiner, George J. (Frontiers in Immunology, 2026)
IntroductionVidutolimod (Vidu) is a nanosized virus-like particle (VLP) composed of the Qβ bacteriophage capsid assembled around a Toll-like receptor 9 (TLR9) agonist. In situ immunization with Vidu through intratumoral injection can induce a systemic anti-tumor immune response and has shown promise in early phase cancer clinical trials. Activation of intratumoral plasmacytoid dendritic cells (pDCs), and their production of type I interferon (IFN), plays a key role in initiating the anti-tumor response to Vidu and is dependent on coating of the VLP by antibodies against the Qβ capsid (anti-Qβ). Here we evaluated the mechanisms responsible for the binding, internalization and response of pDCs to anti-Qb-coated Vidu.MethodsUsing multicolor spectral flow cytometry and imaging flow cytometry, we characterized the association and uptake of anti-Qb-opsonized, fluorescently labeled Vidu by pDCs and other immune cell subsets. Interferon alpha (IFNα) secretion and differentiation marker expression on pDCs after various treatments with anti-Qβ-coated Vidu were evaluated to determine which pDC membrane proteins contribute to Vidu uptake and pDC activation.ResultsAnti-Qb-coated Vidu interacted broadly with immune cells, mediated in most cases by canonical Fcγ receptors (FcγRs), i.e., CD16, CD32 and CD64. A notable exception was in the pDC population where binding was found to also be mediated by BDCA2, a type II C-type lectin. This pDC-specific receptor contributed to internalization of anti-Qβ-coated Vidu and subsequent pDC activation when lower concentrations of anti-Qb were used. In contrast, Vidu coated with higher concentrations of anti-Qb induced significant internalization of BDCA2 and reduced activation of pDCs.DiscussionThese findings indicate BDCA2 plays a dual role in the immune response to Vidu, with the amount of anti-Qb antibody coating Vidu determining whether interaction of Vidu with BDCA2 results in pDC activation or inhibition. This important mechanistic information could influence the design of the next generation of pDC-targeting immunotherapeutic nanoparticles.